2019
DOI: 10.1038/s41598-019-53919-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability does not impact in vitro fertilization success

Abstract: It is unknown whether seasonal variation influences the outcome of in vitro fertilization (IVF). Previous studies related to seasonal variation of IVF were all small sample size, and the results were conflicting. We performed a retrospective cohort study evaluating the relationship between seasonal variability and live birth rate in the year of 2014–2017. Patients were grouped into four seasons (Winter (December-February), Spring (March-May), Summer (June-August), and Autumn (September-November)) according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Because of the Covid-19 pandemic, we were constrained to suspend transfers between March and June 2020. We compared two similar periods between the two years to avoid a potential seasonality bias, even though no significant difference of seasonal variations in the outcomes of IVF was observed in the literature [ 70 , 71 ]. A pending question concerned pregnancies after double embryo transfers, where a 50% agreement was found.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the Covid-19 pandemic, we were constrained to suspend transfers between March and June 2020. We compared two similar periods between the two years to avoid a potential seasonality bias, even though no significant difference of seasonal variations in the outcomes of IVF was observed in the literature [ 70 , 71 ]. A pending question concerned pregnancies after double embryo transfers, where a 50% agreement was found.…”
Section: Discussionmentioning
confidence: 99%
“…Possible limitation of our study is the fact, that AMH is a stable prognostic marker for the amount of oocytes that might be retrieved after stimulation in an IVF/ICSI cycle, but it is a poor marker for predicting a pregnancy [43], as it is only weakly associated with embryo implantation [17]. The majority of studies suggested no statistically association between clinical pregnancy rates or life birth rates [1,4,6,30,34,44], probably due to speci c framework of the studies. However, Brodin et al showed a strong association between AMH and live birth rates after ART [45].These ndings may indicate a relation between AMH, vitamin D and oocyte quality.…”
Section: Discussionmentioning
confidence: 85%
“…A large retrospective cohort study conducted in China included 38,476 women who underwent either fresh or frozen embryo transfer. [ 21 ] The study groups were divided into 3 monthly groups into spring, summer, autumn, and winter. The unadjusted model showed a significant difference in clinical pregnancy rates ( P = 0.027) and embryo cleavage rate ( P = 0.033) with significantly higher rates in summer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 ] In addition, some investigators further reported no significant difference in fertilization, clinical pregnancy, or LBRs following ART in different seasons. [ 19 20 21 ] The lack of consistency in the results may be attributed to the heterogeneity in study population, ART protocols, ethnicity, and regional variations in types and duration of seasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation